Called to Be a Pastor: Issues of Vocation in the Early Modern Period - Maag, Karin (The sixteenth century journal, 2004)
Basing itself on an early-seventeenth-century case of conflict between a pastor and his Calvinist consistory in the Walloon church of Amsterdam, this article examines the issue of pastoral vocation in Calvinist and Reformed churches from the first decades of the Reformation onwards. While churches in the early years tried a variety of expedients in order to locate pastors for the expanding number of congregations, there were clear divergences over appropriate selection procedures. Increasingly, Reformed churches used formal examinations and assessments to determine fitness for ministry. Yet in so doing, they may have lost sight of a more unquantifiable and therefore less controllable aspect of ministry, namely, a pastor's sense of calling or vocation.